Effects of different agricultural systems on soil quality in Northern Limón province, Costa Rica - Cornwell, Emma (Universidad de Costa Rica, 2014)
Conversion of native rainforest ecosystems in Limón Province of Costa Rica to banana and pineapple monoculture has led to reductions in biodiversity and soil quality. Agroforestry management of cacao (Theobroma cacao) is an alternative system that may maintain the agricultural livelihood of the region while more closely mimicking native ecosystems. This study compared physical, biological and chemical soil quality indicators of a cacao plantation under organic agroforestry management with banana, pineapple, and pasture systems; a native forest nearby served as a control. For bulk density and earthworm analysis, 18 samples were collected between March and April 2012 from each ecosystem paired with 18 samples from the cacao. Cacao had a lower bulk density than banana and pineapple monocultures, but greater than the forest (p<0.05). Cacao also hosted a greater number and mass of earthworms than banana and pineapple (p<0.05), but similar to forest and pasture. For soil chemical characteristics, three composite samples were collected in March 2012 from each agroecosystem paired with three samples from the cacao plantation. Forest and pineapple ecosystems had the lowest pH, cation exchange capacity, and exchangeable nutrient cations, while cacao had the greatest (p<0.05). Total nutrient levels of P and N were slightly greater in banana, pineapple and pasture than in cacao; probably related to addition of chemical fertilizer and manure from cattle grazing. Forest and cacao also had greater %C, than other ecosystems, which is directly related to soil organic matter content (p<0.0001). Overall, cacao had more favorable physical, biological and chemical soil characteristics than banana and pineapple monocultures, while trends were less conclusive compared to the pastureland. While organic cacao was inferior to native forest in some soil characteristics such as bulk density and organic carbon, its soil quality did best mimic that of the native forest. This supports the organic cultivation of cacao as a desirable alternative to banana and pineapple monoculture.